Thermodynamic and Kinetic Modelling of Scales Formation at the Soultz-sous-Forêts Geothermal Power Plant - Kunan, Pierce; Ravier, Guillaume; Dalmais, Eléonore; Ducousso, Marion; Cezac, Pierre (Geosciences (Basel), 2021)
Geothermal energy has been a subject of great interest since the 1990s in the Upper Rhine Graben (URG), where the first European Enhanced Geothermal System (EGS) pilot site has been developed, in Soultz-sous-Forêts (SsF), France. Several studies have already been conducted on scales occurring at the reinjection side at the geothermal plants located in the URG. It has been observed that the composition of the scales changes as chemical treatment is applied to inhibit metal sulfate. The purpose of this study was to model the scaling phenomenon occurring in the surface pipes and the heat exchangers at the SsF geothermal plant. PhreeqC, a geochemical modelling software, was used to reproduce the scaling observations in the geothermal plant during exploitation. A suitable database was chosen based on the availability of chemical elements, minerals, and gas. A thermodynamic model and a kinetic model were proposed for modelling the scaling phenomenon. The thermodynamic model gave insight on possible minerals precipitated while the kinetic model, after modifying the initial rates equation, produced results that were close to the expected scale composition at the SsF geothermal plant. Additional laboratory studies on the kinetics of the scales are proposed to complement the current model.